2015
DOI: 10.1039/c4ta04706k
|View full text |Cite
|
Sign up to set email alerts
|

First principles guide to tune h-BN nanostructures as superior light-element-based hydrogen storage materials: role of the bond exchange spillover mechanism

Abstract: We investigate the interaction of molecular hydrogen with light element based ndoped hexagonal boron nitride (h-BN) nanostructures and moreover explore the bond exchange mechanism for spillover of atomic hydrogen using dispersion-corrected density functional theory (DFT-D) calculations. A number of doped configurations were tested and it has been found that co-doping of C and O on h-BN sheet significantly increases the adsorption energy of molecular H 2 . The charge transfer from the n-doped h-BN surface to H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…; in eV) were calculated by using the PW91+D functional (for more details about the calculation method the reader is invited to refer to ref. ). The H 2 –surface distances ( d a ) are in Å.…”
Section: Avenues For Improvementsmentioning
confidence: 99%
See 3 more Smart Citations
“…; in eV) were calculated by using the PW91+D functional (for more details about the calculation method the reader is invited to refer to ref. ). The H 2 –surface distances ( d a ) are in Å.…”
Section: Avenues For Improvementsmentioning
confidence: 99%
“…This was also confirmed by Kumar et al by using dispersion-corrected DFT. [64] They in addition considered co-doping by Ca nd O, and found that the as-modified BN would be much more efficient in storing H 2 compared with the C-, O-, and 2C-doped counterparts ( Figure 5). Notwithstanding these computational achievements, one may regret av ery limited number of experimental evidences.…”
Section: Substitutional Doping Of Bnmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Far from discourage, further and present research is addressed at enhancing the H 2 attachment to such carbon-based structures. In that sense, analogous boron nitride nanotubes and sheets have been explored, 9,10 with adsorption energies not exceeding 1.25 kJ mol -1 according to DF calculations within the Generalized Gradient Approximation (GGA), yet inclusion of van der Waals (vdW) forces may rise this value up to 14.47 kJ mol -1 in h-BN sheets. 9 Another strategy to enhance the H 2 physisorption to adequate levels is to functionalize the carbon or BN based structures, mostly with light alkaline or alkaline earth metals, where Li, Be, and Ca are probably exemplary cases.…”
Section: Introductionmentioning
confidence: 99%